N-myc is frequently activated by proviral insertion in MuLV-induced T cell lymphomas. - van Lohuizen, M (1989)
We report a new common proviral insertion site in murine leukemia virus-induced T cell lymphomas to be N-myc. Proviral activation of N-myc was found in 35% of independently induced primary tumors. The vast majority of the proviral insertions occur within a small segment of the 3'-untranslated region of the N-myc gene, directly downstream of the protein-encoding domain. This results in an increased level of expression of a truncated N-myc mRNA. Together with the previously shown c-myc activation we now find involvement of myc genes in greater than 75% of the primary T cell lymphomas induced by Moloney murine leukemia virus in C57BL10 and BALB/c mice, and show for the first time that N-myc can be over-expressed by a mechanism other than gene amplification.